Prevalence and Factors Associated with Intestinal Parasitic Infections among People with Disabilities in Gem Sub-County, Siaya County - Kenya - Oyoya, Michael Kala (JOOUST, 2023)
Intestinal parasitic infection (IPI) is a worldwide public health concern that has received little attention as compared to other communicable diseases like tuberculosis, COVID-19, HIV and AIDS and malaria. Although, people with disabilities (PWDs) are more susceptible to IPIs they have limited access to adequate healthcare services. At least 0.9 million people in Kenya have disabilities and Siaya county is among the four counties with a high disability prevalence of 4.1%. Gem sub-county has 4.3% PWDs that is twice higher than the national level. The PWDs face person and health system-related factors that negatively affect their health outcomes. Nevertheless, little is known about the prevalence, person-related and health system-related factors associated with IPIs among PWDs in Gem sub-county, Siaya County - Kenya. The three specific objectives include: to determine the prevalence; the person-related factors and the health system-related factors associated with IPIs among PWDs in Gem sub-county, Siaya County. A descriptive cross-sectional study was conducted to investigate the prevalence and factors associated with IPIs among PWDs in Gem sub-county, Siaya County. Multistage sampling was applied to select 191 study participants. The study site was divided into 9 strata based on the existing administrative units. Simple random sampling was then applied to select 2 Community Health Volunteers (CHVs) from each administrative unit as research assistants. Finally, each CHV proportionately and randomly selected eligible study participants from the administrative unit. Primary data on the prevalence of IPI was collected by examination of the stool samples from each study participants using direct saline and iodine mounts and formol-ether concentration to detect intestinal parasites. Structured questionnaires were applied to collect data on the person and health system- related factors associated with IPIs among the study participants. Logistic regression tests were computed to determine the significant association between the variables of interest (α = 0.05). The overall prevalence of IPIs in this study was 46.03%. Ascaris lumbricoides (37.93%) and Entamoeba histolytica (29.89%) were the predominant intestinal parasites. Persons with physical disability (62.07%) and mental disability (32.18%) had the highest prevalence than those with other forms of disability. Person-related factors including soil eating behaviour (COR:2.7, 95% CI: 1.25-5.81, p=0.011) and poor personal hygiene (COR:3.74, 95% CI: 1.65-8.51, p=0.002) were significantly associated with the high prevalence of IPIs. Proper latrine use (p=0.001), drinking treated water (COR: 0.36, 95% CI: 0.19-0.69, P=0.002), regular wearing of shoes (COR:0.37, 95% CI: 0.2-0.68, p=0.001) and handwashing with soap after defecation (COR:0.34, 95% CI: 0.17-0.67, p=0.002) and before eating (COR:0.48, 95% CI: 0.21-0.88, p=0.02) significantly reduced the risk of IPIs. Furthermore, lack of access (COR: 0.42, 95% CI: 0.19-0.94, p=0.035), inefficiency (COR: 2.88, 95% CI: 1.21-6.81, p=0.016) and low quality (COR: 0.55, 95% CI: 0.31-0.97, p=0.041) of healthcare services, are among the health system-related variables that contribute significantly towards the high burden of the IPIs. It is even more complicated to manage the high burden of IPIs especially when associated with some form of disability. These findings provide evidence-based information to the Ministry of Health, people with disabilities and other stakeholders for use in the formulation of policies on prevention and control of IPIs among PWDs.
Keywords: Intestinal Parasitic Infections; People with Disabilities